Perbandingan Algoritma Boosting Untuk Klasifikasi Gaya Belajar Siswa Sekolah Menengah Kejuruan - Ihsan, M Khaerul; Saputri, Dian Syafitri Chani; Sulistianingsih, Neny (STMIK Banjarbaru, 2025)
Education is a planned activity to improve human resources. However, based on interviews at SMKN 2 Mataram, the learning process has not been running optimally because the teaching method is not in accordance with the student learning styles. This study aims to identify students learning styles (Visual, Auditory, and Kinesthetic) using the Boosting method, namely AdaBoost, Gradient Boosting, and XGBoost. Data were obtained from questionnaires that had been tested for validity and reliability, and distributed to 203 students in grades X and XI from the TKJ, RPL, and ULW department. The dataset was divided into tree schemes: 70:30, 80:20, and 90:10. The best result were obtainet from XGBoost in the 70:30 scheme with an accuracy of 0.93, precision of 1.00, recall of 0.97, anf f1-score of 0.97. GradentBoost followed with an accuracy of 0.92, while ADaBoost had the lowest accuracy of 0.80. thus, XGBoost is superior and can be used as a refence in determining learning methods according to student charateristics.Keywords: Boosting Algorithm; Classification; Learning Style; Algorithm Comparison AbstrakPendidikan merupakan aktivitas terencana untuk meningkatkan mutu sumber daya manusia. Namun, berdasarkan wawancara di SMKN 2 Mataram, proses pembelajaran belum berjalan optimal karena metode pengajaran tidak sesuai dengan gaya belajar siswa. Penelitian ini bertujuan untuk mengidentifikasi gaya belajar siswa (Visual, Auditori, dan Kinestetik) menggunakan metode Boosting, yaitu AdaBoost, Gradient Boosting, dan XGBoost. Data diperoleh dari kuesioner yang telah diuji validitas dan reliabilitasnya, dan disebarkan kepada 203 siswa kelas X dan XI dari jurusan TKJ, RPL, dan ULW. Dataset dibagi dalam tiga skema: 70:30, 80:20, dan 90:10. Hasil terbaik diperoleh dari XGBoost pada skema 70:30 dengan akurasi 0.93, precision 1.00, recall 0.97, dan f1-score 0.97. Gradient Boosting menyusul dengan akurasi 0.92, sedangkan ADaBoost memiliki akurasi terendah sebesar 0.80. Dengan demikian, XGBoost lebih unggul dan dapat dijadikan referensi dalam menentukan metode pembelajaran sesuai karakteristik siswa.